Contribution of Nutrients and some Trace Metals from a Huge Egyptian Drain to the SE-Mediterranean Sea, west of Alexandria - EL-RAYIS, O.A.; ABDALLAH, M.A.M. (Mediterranean Marine Science, 2006)
In 2003 the MAP Technical Report Series 141, mentioned the lack of data concerning the flux of water, sediments and pollutants from North-African rivers and from the land-based sources to the Mediterranean Sea.In Egypt, the Omoum drain, after the construction of the Aswan High Dam and the controlling of the Nile River water fl ow, has become one of the main land-based sources regularly discharging its waters (fl ow rate 2547.7 x 106 m3/year) directly into the Mediterranean Sea at EL-Mex Bay, west of Alexandria. Downstream, before it reaches the sea, its water mixes with water effl uent (surplus water) from a neighboring sewage-polluted lake called Lake Maryout, rate 262.8 x 106 m3/year. The present work is a monthly study over a year of levels of concentration of some mainly trace elements (nutrients and some heavy metals) in the proper water of the drain before mixing and in the effl uent from the lake, and calculations of both the concentrations and the corresponding expected loads of these elements contributed by the drain to the sea. The results revealed that the respective loads to the sea are 77380 ton/year for total suspended matter, 823 tons/year for dissolved PO4 -P, 4745 tons/year for inorganic N, 23.7 tons/year for Fe, 3.28 tons/year for Mn, 5.84 tons/year for Cu, 2.9 ton/year for Cd, and 24 tons/year for Zn. The elements loaded by the lake effl uent represent values ranging between 8 and 57.5% of the total load contributed by the drain to the sea. The plant nutrients (ammonia and reactive phosphorus) are of values exceeding 44%.